Rodzina łemkowska dawniej i dziś - Orłowska, Beata (Karkonoska Państwowa Szkoła Wyższa, 2011)
The functioning of Lemko families of the past and the present in the context of preservation of cultural identity in discussed in the article. The observing of the most important holidays after the resettlement to western Poland is described, among other issues. The historical context of the resettlement of the Lemko people to western Poland is discussed.
Keywords: Lemko; family; resettlement; cultural identity